Out of Refugia: Population Genetic Structure and Evolutionary History of the Alpine Medicinal Plant Gentiana lawrencei var. farreri (Gentianaceae) - Fu, Peng-Cheng; Ya, Hui-Yuan; Liu, Qi-Wei; Cai, Hui-Min; Chen, Shi-Long (Frontiers in Genetics, 2018)
Understanding the genetic structure and evolutionary history of plants contributes to their conservation and utilization and helps to predict their response to environmental changes. The wildflower and traditional Chinese and Tibetan medicinal plant Gentiana lawrencei var. farreri is endemic to the Qinghai-Tibetan Plateau (QTP). To explore its genetic structure and evolutionary history, the genetic diversity, divergence, and demographics were analyzed in individuals from 31 locations across the QTP using 1 chloroplast marker and 10 nuclear microsatellite loci. High genetic diversity was detected in G. lawrencei var. farreri, and most of the genetic variance was found within populations. Values of FST in G. lawrencei var. farreri from nuclear microsatellite and chloroplast data were 0.1757 and 0.739, respectively. The data indicated the presence of isolation by distance. The southeast edge of the QTP was the main refugium for G. lawrencei var. farreri, and one microrefugium was also detected in the plateau platform of the QTP. Both nuclear microsatellite and chloroplast data indicated that the populations were divided into two geographically structured groups, a southeast group and a northwest group. The current genetic pattern was mainly formed through recolonization from the two independent refugia. Significant melt was detected at the adjacent area of the two geographically structured groups. Approximate Bayesian computation showed that the northwest group had diverged from the southeast group, which then underwent population expansion. Our results suggest that the two-refugia pattern had a significant impact on the genetic structure and evolutionary history of G. lawrencei var. farreri.